Why and how do project management offices change? A structural analysis approach. Issue 5 (July 2018) - Bredillet, Christophe; Tywoniak, Stephane; Tootoonchy, Mahshid
Abstract: The growing popularity of Project Management Offices (PMOs) as organizational structures is grounded in the assumption they support more efficient and effective project management for better strategy implementation. However, research emphasizes they fail to deliver expected value: their unstable nature precludes the delivery of long-term benefits. This is compounded by the absence of a theory of PMO change and adaptation. Recent research, taking a co-evolution lens rooted in evolutionary theory, suggests that PMOs should be studied in relation to the broader organizational context, in order to better capture the dynamic interplay and fit between them. In this study, taking a routine perspective as micro-foundation and unit of analysis, we focus on the co-evolution between PMO and Project Portfolio Management (PfM) as organizational capability for six case studies. A structural analysis of the relational routines' system between PMO, PfM and the Organizational context allow us to unveil dynamics at stake, i.e. why and how changes occur, as well as eigen behaviors and the changing states of various routines elements (influential, mediating, dependent or not-influential). This study makes five contributions. We show that: 1) PMO and PfM can be conceptualized as collections of routines, 2) PMO and PfM co-evolve over time to adapt to organizational context influence, 3) the co-evolution of a routines' system, abstracted as a non-trivial machine, exhibits an eigen behavior, 4) applying a structural analysis approach allows to simulate the dynamics of a routines' system and to unveil the role of key routine elements and 5) eigen values of routines' systems allow to characterize their eigen behavior. Highlights: PMO and PfM can be conceptualized as collections of routines PMO and PfM co-evolve over time to adapt to organizational context influence the co-evolution of a routines' system, abstracted as a non-trivial machine, exhibits an eigen behavior a structural analysis approach allows to simulate the dynamics of a routines' system and to unveil the role of elements Eigen values of routines' systems allow to characterize their eigen behavior.